RESPON PERTUMBUHAN DAN HASIL JAGUNG (Zea mays L.) TERHADAP PEMBERIAN PUPUK ORGANIK CAIR (POC) DAN PUPUK UREA - Awidiantini, Rully; Nurmalasari, Yanti; Qomariah, Lailatul (Universitas Islam Madura, 2024)
ABSTRACT The need for corn in Indonesia is currently quite large and increasing. With the increasing need for corn, corn cultivation must use good prospects, one of which is the use of fertilizer. This research aims to enable students and the community to know how to produce good corn production by using local varieties with organic fertilizer and inorganic fertilizer treatment and also to know how to use a combination of organic and inorganic fertilizer on corn plants. This research used a non-factorial completely randomized design (CRD) with 5 treatments with 4 replications with various dosage levels of liquid organic fertilizer with a combination of Urea fertilizer, namely: P1: Urea 6 g + 0 ml POC, P2: Urea 6 g + POC 10 ml /L POC, P3: Urea 6 g + POC 20 ml/L POC, P4: Urea 6 g + POC 30 ml/L POC, P5: Without urea and without POC. The results of the research show that treatment of Urea fertilizer with Liquid Organic Fertilizer from cow dung can increase the growth and good yields of corn plants in the parameters of plant height, leaf length, number of cobs, wet weight of fruit, dry weight of fruit, number of rows/cobs, number of seeds/ cobs by P3=(Urea 6 g + POC 20 ml/L POC) with no significant difference, while the resulting parameters were significantly different from the parameters obtained for the number of cobs on corn plants.